E-066 A favorable profile for selecting acute ischemic stroke patients for thrombolytic therapy. (4th July 2012) - Moradzadeh, N; Sharma, J; Vargas, E; Jung, R; Koo, B; Blackham, K
Abstract : Background: There is currently an intense interest in defining predictive profiles from MRI based diffusion/perfusion information for acute ischemic stroke patients. Perfusion/diffusion ratio (mismatch ratio) and penumbra volumes are factors used to select patients for thrombolysis. The current literature considers a mismatch ratio of 1.2 as the minimum for thrombolysis. There is much debate, however, as to how mismatch ratios and penumbra volumes affect patient outcome. Methods: 31 acute ischemic stroke patients were selected at random and had their presenting acute stroke-protocol MRI processed through OLEA Medical's PerfScape, which calculated the penumbral volume and mismatch ratio, using a Tmax of 4 s. A mismatch ratio of 1.2–4.5 with a penumbra volume >80 cc was labeled as a Favorable Profile (FP). NIHSS scores were collected both at stroke presentation and at time of discharge. An improvement of NIHSS ≥4 at time of discharge was considered a good outcome. Results: Eight patients were found to have a FP with a mismatch ratio between 1.2 and 4.5 and a penumbra volume >80 cc. Twenty-three patients did not have an FP. Of the eight patients with an FP, all 8 had an improvement of ≥4 in their NIHSS score. Of the 23 patients who did not have an FP, 7 had an improvement of ≥4 in their NIHSS score, while 16 had no improvement or an improvement of <4 in their NIHSS score, (p=0.0008). Furthermore, a homogenous subset of patients (N=20) who underwent thrombolytic therapy and achieved TIMI 2 or greater recanalization, showed similar findings (p=0.02) Conclusion: This small study demonstrates that our definition of a favorable MRI perfusion profile in ischemic stroke patients (mismatch ratio of 1.2–4.5 and a penumbra volume >80 cc) was associated with a good outcome at discharge, for all patients as well as an endovascularly treated homogeneous subset. Furthermore, the clinical application of this upper limit of 4.5 for the mismatch ratio warrants further investigation. Competing interests: None.